نصوص کے تناظر میں تجرد کے اسباب و اثرات: Caused and Effects of Abstinence in the Context of Holy Quran - Dr. Shazia Ramzan,; Ainee Rubab, (Al Manhal Research Journal, 2024)
Islam is a complete code of life that guides us in every sphere of life. If all the religions of in the world are studied, Islam is the only religion which takes both the religion and the world together. In front of us is the biography of the last and final Prophet, Hazrat Muhammad (PBUH), how he conquered, people became Muslims, and at the same time, he also married and lived his remarkable family life. Marriage in Islam is Sunnah and it is not said anywhere that do not marry. The following research article also focuses on the fact that there is no monasticism in Islam. Islam rejects celibacy and such practice that is coming in the society from the others such as people say that our career is important for us, we do not get married. Whereas, in the light of the Qur'an and Hadith, this has been said to get married.